PENERAPAN PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN PEMAHAMAN KONSEP LUAS PERMUKAAN BANGUN RUANG DAN MENGATASI KEJENUHAN PADA SISWA KELAS VI A SDI LABAT KOTA KUPANG TAHUN PELAJARAN 2021/2022 - Melilla Eviana (Jurnal Lazuardi, 2023)
This article is the result of classroom action research on the application of this differentiated learning as an effort to provide educational services according to the needs of students in the classroom. This study aims to describe the application of differentiated learning in class VI which is hypothesized to be able to improve students' ability to understand the concept of surface area and overcome saturation in students who already understand the concept of geometric surface area. This research was conducted at Inpres Labat Elementary School with the research subjects being all students of class VIa Pres Elementary School. This classroom action research uses the Kemmis and Taggar models. Data collection was carried out using questionnaires, observations, and written tests. The data is tabulated and analyzed quantitatively and qualitatively. The results of this study indicate an increase in learning outcomes obtained through written tests in learning evaluation, an increase in learning outcomes as an indicator of increased understanding of the concept of geometric surface area and an increase in student learning activity as an indicator of students being maintained from saturation. In the initial conditions, the average student learning outcomes were 70.77 with 50% mastery of the class, there was an increase in cycle 1 where the average learning outcomes became 73 with 76.92% mastery and in cycle 2, the average learning outcomes increased 75.5 and class completeness 88.46%. Other students who have not finished have also experienced an increase in learning outcomes in the initial disbandment state. Keywords: differentiation learning, flat shape, surface area.